The use of laser scanners in survey work for the design of linear and areal structures - Kusainova G. D, Кусаинова Г. Д; Shakabaev E.O., Шакабаев Е.О. (Рroblems of engineering and professional education, 2023)
This article discusses the scientific technical characteristics, progress and effectiveness of the use of modern groundbased laser scanners Leica ScanStation2, as well as their application in the field of geodetic support in survey works for the construction of linear and area facilities